Creative therapy : activities with chirldren and adolescents - Hobday, Angela. (Australian Council for Educational Research, 1998)
This book is about: Getting to know you; Feelings; Increasing motivation to change; Becoming less stressed; Learning new skills; Improving coping skills; Coming to terms with loss; Understanding my family; Promoting positive self-esteem; and Reviewing progress.